A coded convolutional spreading CDMA system with turbo equalization for downlink transmission over a frequency selective fading channel - Weerasinghe, N.; Watanabe, S.; Hashimoto, T.; Itoh, S. (IEEE transactions on communications, 2009)
In this paper, a coded convolutional spreading codedivision multiaccess with cyclic prefix (CS-CDMA/CP) system in conjunction with iterative receivers is proposed for synchronous downlink transmission over frequency selective fading channels and its performance is compared with the uncoded CS-CDMA/CP employing maximum-likelihood sequence estimation (MLSE) receiver as well as with the conventional coded direct sequence CDMA (DS-CDMA) employing (maximal ratio combining-) MRC-RAKE. Contrary to the uncoded CSCDMA/ CP system which suffers from performance degradation at low signal-to-noise power ratios (SNRs), it is demonstrated that the proposed scheme can attain almost the full path diversity gain over all SNRs with single-user complexity. Compared with the coded DS-CDMA system with single-user receivers, the proposed system is free from multiuser interference (MUI) whenever the multipath delay of the channel does not exceed the designed maximum delay. It is also demonstrated, moreover, that the proposed system shows a robust performance even if the channel length exceed the designed maximum delay slightly. Because of the subblock structure of CS-CDMA/CP, the proposed system can utilize time-diversity effects, when the channel subjects fast fading, and this greatly improves the resultant performance. Finally, it is shown that the receiver complexity of the proposed system is compared quite favorably with the iterative multiuser receivers for coded DS-CDMA systems of comparable performance.